Get detailed and reliable answers to your questions with IDNLearn.com. Get the information you need from our community of experts who provide accurate and thorough answers to all your questions.

Simplify the following expression:

[tex]\left(3a + 8b^3\right)^2[/tex]


Sagot :

To solve the problem of expanding [tex]\(\left(3a + 8b^3\right)^2\)[/tex], we need to apply the principles of algebraic expansion. This involves using the formula for the square of a binomial:

[tex]\[ (x + y)^2 = x^2 + 2xy + y^2 \][/tex]

In this scenario, we have:
- [tex]\(x = 3a\)[/tex]
- [tex]\(y = 8b^3\)[/tex]

So, we need to expand [tex]\((3a + 8b^3)^2\)[/tex]. Applying the formula gives us:

[tex]\[ (3a + 8b^3)^2 = (3a)^2 + 2(3a)(8b^3) + (8b^3)^2 \][/tex]

Now, let's break this down step by step.

1. Calculate [tex]\((3a)^2\)[/tex]:
[tex]\[ (3a)^2 = 9a^2 \][/tex]

2. Calculate [tex]\(2(3a)(8b^3)\)[/tex]:
[tex]\[ 2(3a)(8b^3) = 2 \cdot 3 \cdot 8 \cdot a \cdot b^3 = 48ab^3 \][/tex]

3. Calculate [tex]\((8b^3)^2\)[/tex]:
[tex]\[ (8b^3)^2 = 64b^6 \][/tex]

Finally, combine all the terms we have calculated:

[tex]\[ (3a + 8b^3)^2 = 9a^2 + 48ab^3 + 64b^6 \][/tex]

Therefore, the expanded form of [tex]\((3a + 8b^3)^2\)[/tex] is:

[tex]\[ 9a^2 + 48ab^3 + 64b^6 \][/tex]